Delignification of Rice Husk by Microwave Assisted Chemical Pretreatment - Laghari, S. M.; Tunio, M. M.; Laghari, A. Q.; Laghari, A. J.; Ali, A. M. (Engineering, Technology & Applied Science Research, 2018)
Rice husk has the potential to be used as a source of alternative energy e.g. as biofuel. Its high lignin content, however, poses difficulty to this use. This study investigates the use of microwave assisted acidic and alkaline pretreatment methods to improve the characteristics of rice husk for energy production. The use of microwave assisted 3.5% NaOH provided optimum pretreatment of rice husk; the lignin content was reduced from 17.8 to 10.2%, the cellulose content increased from 38.6 to 59.3% and the C/N ratio was within the optimum range of 25-35. The results showed enhanced potential of biofuel production from rice husk by this pretreatment.